2019
DOI: 10.1007/s10334-019-00809-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the interobserver reproducibility of different regions of interest on multi-parametric renal magnetic resonance imaging in healthy volunteers, patients with heart failure and renal transplant recipients

Abstract: Objective To assess interobserver reproducibility of different regions of interest (ROIs) on multi-parametric renal MRI using commercially available software. Materials and methods Healthy volunteers (HV), patients with heart failure (HF) and renal transplant recipients (Tx) were recruited. Localiser scans, T1 mapping and pseudo-continuous arterial spin labelling (pCASL) were performed. HV and Tx also underwent diffusion-weighted imaging to allow calculation of apparent diffusion coefficient (ADC). For T1, pCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Absolute RBF values in this study are comparable to those reported by Khatir et al 30 in healthy subjects and Jin et al using breath hold PC, 31 Gillis et al 28 and Shirvani et al 32 using ASL with FAIR labeling and Rankin et al 33 using the same pCASL labeling used in our study. Nevertheless, it is surprising that mean RBF of our healthy participants was substantially lower than reference values in the literature.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Absolute RBF values in this study are comparable to those reported by Khatir et al 30 in healthy subjects and Jin et al using breath hold PC, 31 Gillis et al 28 and Shirvani et al 32 using ASL with FAIR labeling and Rankin et al 33 using the same pCASL labeling used in our study. Nevertheless, it is surprising that mean RBF of our healthy participants was substantially lower than reference values in the literature.…”
Section: Discussionsupporting
confidence: 90%
“…Twenty-five patients (16 males and 9 females, mean age (interquartile range) of 65 (56-72) years) were analyzed and included for comparison. Five healthy volunteers (one male and four females, mean age [interquartile range] of 39 [31][32][33][34][35][36][37][38][39][40] years) completed the four visits at an average of 4 months apart (range between 2 and 7 months).…”
Section: Participant Demographicsmentioning
confidence: 99%
“…Cortical RBF values obtained in this study are in line with values described in the literature, although only a few articles have previously reported RBF in renal allografts measured with PCASL. Yu et al 25 reported an RBF of 144.73 (49.33) ml/min/100 g in a group of stable patients with a mean eGFR of 72 ml/min/1.73m 2 , using a PCASL 3D-FSE spiral; Wang et al 26 measured an RBF of 204.7 (44.9) ml/min/100 g in stable patients whose eGFR was 77.1 (15.1) ml/min/1.73m 2 , using a similar PCASL sequence; Rankin et al 27 showed an RBF of 239 (84) ml/min/100 g measured with PCASL 3D-TGSE in a group of transplant patients with a mean eGFR of 48 ml/min/1.73m 2 and Ahn et al 28 obtained an RBF of 358 (36) ml/min/100 g with a PCASL BSSFP sequence employing several postlabeling delays, in a study performed shortly after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the midslice of the kidney was assumed to be representative enough of the whole kidney in several previous DWI studies. [36][37][38] The datasets were smoothed with an isotropic 3 × 3 Gaussian kernel to increase SNR. Cortical and medullary ROIs and the tumor and cyst volumes were then manually segmented on the b 0 images by an experienced radiologist (a.l., 11 years of experience) in the open-source image segmentation toolbox ITK-SNAP (Version 3.8.0).…”
Section: Discussionmentioning
confidence: 99%
“…Only a single image slice containing the center of the right kidney was selected for further analysis because (1) it was not affected by respiratory motion compared with the remaining slices; (2) it contained the maximum parenchymal area, which allowed the largest cortical and medullary regions of interest (ROIs) to be obtained; and (3) both cortex and medulla were clearly visible thus enabling a reliable segmentation. Furthermore, the midslice of the kidney was assumed to be representative enough of the whole kidney in several previous DWI studies 36‐38 . The datasets were smoothed with an isotropic 3 × 3 Gaussian kernel to increase SNR.…”
Section: Methodsmentioning
confidence: 99%